Implementation of QIS (Qasiimatun) as A Secure Educational and Governance-based Cashless Transaction System in The Madrasah Environment - Mohamad Santoso; Suryani; Azizah Nur Rohmah (Jurnal Isema : Islamic Educational Management, 2026)
Technological advancements in education have encouraged madrasahs to adopt management systems that are safer, more organized, and educationally oriented. Previous studies on cashless systems in educational institutions have mainly focused on transaction efficiency and digital payment technology, while limited attention has been given to their role in institutional governance, character education, and environmental management at the primary madrasah level. At MI Al-Islamiyah, conventional cash-based canteen transactions created managerial challenges, including limited supervision of students’ spending behavior, unhealthy food sales, and increasing plastic waste. Therefore, this study aims to describe the implementation of QIS as a cashless transaction system in supporting security, transparency, student character development, and canteen governance. This study employed a qualitative descriptive approach using observations, interviews, and documentation. The findings show that QIS improves transaction security and transparency, promotes discipline and financial awareness among students, and strengthens institutional supervision of student activities. In addition, QIS supports healthier and more environmentally friendly canteen management through the reduction of unhealthy packaged products and single-use plastic waste. These findings indicate that context-adaptive cashless systems can function not only as payment mechanisms but also as governance instruments that support environmental management and character education in madrasahs.